Anemia and severe malnutrition in a young patient: Beliefs and customs disguised as science - Velasco Castro, Julio César; Sotaban Piraban, Luz Nelba; Vargas Rodríguez, Ledmar Jovanny; Holguín Barrera, Mónica Liseth; Gracia Agudelo, Lorena (Interdisciplinary Journal of Epidemiology and Public Health, 2024)
Introduction: Malnutrition and anemia are an important cause of morbidity and mortality in Colombia and the world. Among the causes and/or risk factors can be related to ethnic and indigenous groups, which due to their customs and beliefs are a limitation to consult health centers and, on the contrary, turn to individuals with social prestige within a community “shaman” in search of therapeutic behaviors, which is a barrier to the health system and a public health problem Objective: To present the clinical case of an adolescent patient with a fatal outcome due to inadequate management of severe anemia and severe malnutrition Clinical case:17-year-old teenager living with her elderly parents in a rural area was found at home with altered consciousness, unquantified fever, global headache, and epistaxis, referred with a diagnosis of severe anemic syndrome with hemoglobin of 3.3 g/dL, and severe malnutrition. He was admitted to the emergency room in cardiorespiratory arrest, advanced resuscitation maneuvers were started, but no vitality response was obtained, declaring death Conclusion: The management of anemia in rural areas is carried out through different beliefs and cultures that are transmitted from generation to generation, which involve a series of baths, concoctions, ointments, and salves, which due to lack of knowledge of the families go to empirical healers in the regions to perform mixtures of plants or rituals to heal the symptoms, omitting the importance of seeking timely care at medical centers.